Factors Associated With New‐Onset Depression Following Ischemic Stroke: The Women's Health Initiative. Issue 2 (February 2017) - Salinas, Joel; Ray, Roberta M.; Nassir, Rami; Lakshminarayan, Kamakshi; Dording, Christina; Smoller, Jordan; Wassertheil‐Smoller, Sylvia; Rosand, Jonathan; Dunn, Erin C.
Abstract : Background: Psychosocial characteristics have a strong effect on risk of depression, and their direct treatment with behavioral interventions reduces rates of depression. Because new‐onset poststroke depression (NPSD) is frequent, devastating, and often treatment‐resistant, novel preventive efforts are needed. As a first step toward developing behavioral interventions for NPSD, we investigated whether prestroke psychosocial factors influenced rates of NPSD in a manner similar to the general population. Methods and Results: Using the Women's Health Initiative, we analyzed 1424 respondents who were stroke‐free at enrollment and had no self‐reported history of depression from enrollment to their nonfatal ischemic stroke based on initiation of treatment for depression or the Burnam screening instrument for detecting depressive disorders. NPSD was assessed using the same method during the 5‐year poststroke period. Logistic regression provided odds ratios of NPSD controlling for multiple covariates. NPSD occurred in 21.4% (305/1424) of the analytic cohort and varied by stroke severity as measured by the Glasgow scale, ranging from 16.7% of those with good recovery to 31.6% of those severely disabled. Women with total anterior circulation infarction had the highest level (31.4%) of NPSD while those with lacunar infarction had the lowest (16.1%). Prestroke psychosocial measures had different associations with NPSD depending on functional recovery of the individual. Conclusions: There is a difference in the relationship of prestroke psychosocial status and risk of NPSD depending on stroke severity; thus it may be that the same preventive interventions might not work for all stroke patients. One size does not fit all.